Navigating the Regulatory Maze: GDPR Rules for Medical AI in Europe - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into medical practice promises a revolution in diagnostics, treatment, and patient care. From sophisticated ima...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Medical AI